Using impulse to measure intensity during on-water kayaking. Abstract from VIII international congress of coaches of sprint canoeing 2022, Pontevedra, Spain - de Zee, M.; Kristiansen, M. V.; Lauridsen, H. B.; Klitgaard, K. K. (University of Aalborg, 2022)
Background: Mobile power meters in cycling have been around since the 1980's and provide a reliable and valid measure of the cyclists' power output. The cyclists' power output is an objective measure of intensity and is independent of the weather conditions and slope. Moreover, it does not have a time delay like a physiological measure (e.g. heart rate). In cycling it is relatively straightforward to calculate the power by measuring the torque on the crank and the angular velocity given by cadence using the following equation: P = T * w Where P is the power, T is the torque on the crank and w is the angular velocity. In kayaking, however, the measurement of power as an objective measure of intensity is a lot more complicated. Here, one would use the linear form of power: P = F * v Here, P is again the power, F could either be the paddle force or the force on the footrest. And v is the velocity. The question is though, the velocity of what? A logical choice would be the velocity of the kayak itself. However, the velocity of the kayak is heavily influenced by environmental conditions. Therefore, we would not obtain an objective measure of the athlete's intensity. The company One Giant Leap claim to measure power in the paddle, but the algorithm used for determining velocity is confidential and not transparent, which makes it difficult to interpret their measures. An alternative could be to calculate the impulse of the paddle force or footrest force over a certain time period. Klitgaard et al. showed a high correlation between the impulse over 10 seconds of the footrest forces and the velocity of the kayak. In this work, we propose an alternative method to measure the intensity of a kayaking athlete using impulse.